2022
DOI: 10.5001/omj.2022.91
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for 28 Days Hospital Readmission: A Retrospective Study from Oman

Abstract: Objectives: We sought to evaluate the incidence of 28-day hospital readmission in a tertiary hospital in Oman and identify potential factors associated with increased risk of hospital readmission. Methods: We conducted a retrospective study of all adult patients (≥ 18 years) admitted under the care of the General Internal Medicine unit from 1 June to 31 December 2020 at Sultan Qaboos University Hospital. Elective admissions and COVID-19 infection-related admission were excluded from the study. Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…While many studies have reported a higher readmission rate associated with delirium [ 7 , 9 ], our findings do not demonstrate this relationship. There is an overall elevated hospital readmission rate among both groups with delirium and without delirium, which was previously observed in patients admitted under the care of the General Internal Medicine Unit at SQUH, and this could be attributed to the tertiary hospital setting, where more severely ill patients with complex medical conditions are usually admitted [ 16 , 34 ].…”
Section: Discussionmentioning
confidence: 89%
“…While many studies have reported a higher readmission rate associated with delirium [ 7 , 9 ], our findings do not demonstrate this relationship. There is an overall elevated hospital readmission rate among both groups with delirium and without delirium, which was previously observed in patients admitted under the care of the General Internal Medicine Unit at SQUH, and this could be attributed to the tertiary hospital setting, where more severely ill patients with complex medical conditions are usually admitted [ 16 , 34 ].…”
Section: Discussionmentioning
confidence: 89%
“…SQUH is a 600-bed multispecialty-teaching tertiary hospital that provides care for parts of the Muscat and Al-Batinah governorates. It is the main referral center for all regional hospitals in Oman [ 9 , 10 , 11 ]. The study included all patients aged 65 years and older admitted to acute medical ward units from 1 January 2022 to 31 May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…This was a prospective cohort study conducted at Sultan Qaboos University Hospital (SQUH) from June 8, 2022, to October 25, 2022, involving hospitalized adult patients (≥18 years) under the care of the general internal medicine units [ 15 ]. SQUH is an academic tertiary hospital with a capacity of 600 beds and provides multispecialty care for inpatients from all areas of Oman [ 15 ].…”
Section: Methodsmentioning
confidence: 99%